Use of Selective Hemosorption and Hemodiafiltration in a Patient with Toxic Rhabdomyolysis Complicated by Acute Kidney Injury - S. V. Masolitin; M. A. Magomedov; T. G. Kim; I. N. Tyurin; V. M. Smetanina; E. Yu. Kalinin; D. N. Protsenko (Вестник анестезиологии и реаниматологии)
Rhabdomyolysis (RM) is a clinical and laboratory syndrome accompanied by systemic endotoxicosis, a consequence of myocyte destruction and is manifested by acute kidney injury (AKI). The use of extracorporeal detoxification in the early stages of AKI is currently not recognized due to the lack of proven effectiveness.The objective: to demonstrate the effectiveness of selective hemoperfusion (HP) and hemodiafiltration (HDF) in a patient with toxic RM complicated by AKI.Subjects and methods. The article presents a clinical observation of an 18-year-old patient after the use of 4-methylmethcathinone (mephedrone) with development of AKI. Clinical, laboratory, diagnostic, toxicological and instrumental methods of examination were used. HP and HDF were used together with standard intensive therapy.Results. Combined use of HP and HDF was accompanied by regression of markers of endotoxicosis and AKI. A decrease in myoglobin level was noted by 50.3%, 80.3% and 94.1%, respectively, after the 1st and 2nd procedures and by the 5th day. CPK (creatine phosphokinase) decreased by 47.7%, 81.5% and 97.8%, respectively. Cystatin-C went down by 19.3%, 39.9% and 69.9%, respectively.Conclusions. Earlier and justified use of HP and HDF was accompanied by a rapid improvement of clinical and laboratory parameters, which is reflected in the duration of ICU stay, hospital stay and the outcome of the disease in general.